The Utility of the Child and Adolescent Functional Assessment Scale (CAFAS) in Identifying Outcomes of Students with Emotional Disturbance Served in a Day Treatment Program - Moisio, Mitchell D. (2009)
This study investigated student outcomes by analyzing archival PEP client data from the Child and Adolescent Functional Assessment Scale (CAFAS Hodges, 2000). Participants were students with severe emotional and behavioral problems, being served by the Positive Education Program's (PEP) Day Treatment Centers in a midwestern urban center. The CAFAS is a multidimensional rating scale that measures degree of behavioral and emotional impairment across domains in children and adolescents. In addition to subscale and total score analysis, the CAFAS permits analysis of subscale score results in terms of CAFAS Tiers that represent different client types (Hodges, 2004). Hodges (2004) indicated that CAFAS Tiers are a research-based way of assigning clients to diagnostic groups based on the level of impairment in their functioning. CAFAS Tiers have multiple potential utilities which include screening clients for serious problems (i.e., self-harm potential), linking research-based treatments to specific client needs, and assisting agencies with staff training needs and cost allocation decisions (Hodges, 2003a, 2004). This study investigated the utility of the CAFAS in identifying outcomes for PEP students (aka: children, clients, youths) as a function of their CAFAS Tier type. PEP clients' CAFAS Tier type and change in CAFAS scores were compared over a one year period. Results showed that four out of five Tier types demonstrated significant score reduction between first and last CAFAS. Tier groups with highest impairment (i.e., highest overall CAFAS scores at intake) showed the greatest amount of score reduction from first to last CAFAS. The Thought Problems and Delinquency Tiers remained significantly impaired on the Thinking and Community subscales. Lastly, the membership in the severe Tiers' groups at intake decreased by last CAFAS - except for the Thought Problems Tier. Potential benefits of this study include (a) a means to more closely analyze PEP students' outcomes, (b) a basis to modify treatment protocols, and (c